On the use of thermal forces to probe kinesin’s response to force - Chang, Chuan; Zheng, Tiantian; Nettesheim, Guilherme; Song, Hayoung; Cho, Changhyun; Crespi, Samuele; Shubeita, George (Frontiers in Molecular Biosciences, 2023)
The stepping dynamics of cytoskeletal motor proteins determines the dynamics of cargo transport. In its native cellular environment, a molecular motor is subject to forces from several sources including thermal forces and forces ensuing from the interaction with other motors bound to the same cargo. Understanding how the individual motors respond to these forces can allow us to predict how they move their cargo when part of a team. Here, using simulation, we show that details of how the kinesin motor responds to small assisting forceswhich, at the moment, are not experimentally constrained-can lead to significant changes in cargo dynamics.Using different models of the force-dependent detachment probability of the kinesin motor leads to different predictions on the run-length of the cargo they carry. These differences emerge from the thermal forces acting on the cargo and transmitted to the motor through the motor tail that tethers the motor head to the microtubule. We show that these differences appear for cargo carried by individual motors or motor teams, and use our findings to propose the use of thermal forces as a probe of kinesin's response to force in this otherwise inaccessible force regime.